Foliar dewdroplet–induced redox cascades promote early flowering in Brassicaceae plants - Yu Zheng; Bolei Chen; Chun Bao; Yu Xia; Changli Zeng; Maoyong Song; Jianbo Shi; Ligang Hu; Yongguang Yin; Xiaoyun Cui; Juline Auverlot; Jean-Philippe Reichheld; et al. (Proceedings of the National Academy of Sciences, 2026)
Atmospheric water inputs such as dew are often overlooked in plant biology. We show that foliar dewdrops act as biochemical microreactors that trigger flowering in Arabidopsis thaliana , a small plant from the mustard family ( Brassicaceae ). These droplets generate reactive oxygen species that induce intracellular nitric oxide accumulation, initiating a redox cascade that suppresses the biosynthesis of abscisic acid, which contributes to the regulation of flowering time. This occurs via S-nitrosylation-mediated activation of histone deacetylase 19, which silences AAO3 and ABA2 . Analysis of over 12 million field records across the Brassicaceae family reveals a global correlation between dew point temperature and flowering time. These findings identify dewdrop chemistry as an unrecognized environmental cue that regulates developmental timing in plants.